Unveiling biomarkers for postharvest resilience: the role of canopy position on quality and abscisic acid dynamics of ‘Nadorcott’ clementine mandarins - Navarro-Calderón, Ángela; Magwaza, Lembe S.; Terry, Leon A.; Alamar, M. Carmen (Frontiers in Horticulture, 2024)
Clementine mandarins are categorised as non-climacteric fruit because they do not exhibit an increase in respiration rate and ethylene production during ripening. Recent studies have suggested that abscisic acid (ABA), a distinct ripening hormone, plays a pivotal role in the postharvest behaviour of this fruit. The present study aimed to identify biomarkers for enhancing the postharvest durability and flavour retention of imported ‘Nadorcott’ clementines (Citrus reticulata Blanco). To achieve this goal, an experiment was designed to investigate pre- and post-harvest factors influencing quality of clementine fruit, encompassing both physiological and biochemical aspects. Furthermore, the study investigated the role of ABA and ABA catabolites in the fruit senescence process. Clementines from four different canopy positions, namely the upper outside, upper inside, lower outside, and lower inside, were manually harvested at different horticultural maturity. The study was conducted over two harvest times, specifically in March (mid-season) and April (end of season). Harvested fruit samples were stored for six weeks in a cold room with temperature and relative humidity set at 8.5±0.5 °C and 85±2%, respectively. Various physiological (i.e. respiration rate), organoleptic (i.e. rind colour, total soluble solids, and titratable acidity) and biochemical (i.e. individual sugars and organic acids, abscisic acid as its catabolites) variables were measured bi-weekly. Sensory evaluation and consumer survey were conducted during the fourth week of storage. Results showed that, at the end of storage, fruit located on the inside of the canopy had a significantly higher respiration rate and lower concentration of sugars than outside fruit, resulting in a shorter shelf-life. At the same time, inside fruit showed a higher concentration of ABA and ABA catabolites than outside fruit, coinciding with a lower consumer acceptance score for external appearance, aroma, and flavour. For the first time, the key biomarkers affecting resilience and flavour retention, notably the higher ABA concentration and lower sugar levels in inner canopy fruit, resulting in a shorter shelf-life and reduced consumer acceptance were unveiled. This research not only provides valuable insights for the citrus industry but also unveils the intricate relationship between fruit quality, ABA, and ABA catabolites during senescence and consumer acceptance.